Efeitos indiretos das aranhas Peucetia spp. (Oxyopidae) e Misumenops argenteus (Thomisidae) no sucesso reprodutivo de Trichogoniopsis adenantha (DC) (Asteraceae) e no comportamento das guildas associadas à planta - Grisolia, Bruno Barufatti [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Although predators may exert different effects on the behavior of pollinators, parasitoids and phytophagous, little is known about its effects on the risk behavior of these three guilds in the same system. We performed a experimental study to investigate the contrast in foraging behavior between phytophagous, pollinators and parasitoids, manipulating an atmosphere of predation risk on reproductive branches of Trichogoniops adenantha (DC) in the Serra do Japi, Jundiaí, SP. For this, we compared the number of visits to flowers with and without predators. Additionally, we used two species of spiders, Peucetia rubrolineata (Oxyopidae) and Misumenops argenteus (Thomisidae), which use different hunting strategies and forage in different parts of plant. Phytophagous decrease over 50 % of visits when exposed to predator, and avoided carrying flowers indistinctly with P. rubrolineata or M. argenteus. Among the pollinators, predators recognition is taxa specific. In this case, only the bees avoided flowers with M. argenteus, which decreased 60% in the number of its visits. We purpose that the contrast among guilds occur due to the existence of different taxonomic groups. These data provide a new perspective for studies of predation risk, demonstrating that the effect of predators can be distinguished according to the guild observed in the system. How different guilds may cause distinct effects for plant reproductive success, it is important to contemplate the contrast effects of risk behavior among guilds in studies that focus on trophic cascades. The constrating results observed for the different guilds, in particular, the fact of the phytophagous avoiding plants with spiders can be indirectly positive for the reproductive success of plant (i.e. the presence of spiders could influence biotic protection of the plant). Most studies on biotic protection of a plant uses only one kind of predator . However, a current challenge for ecology is to...

Embora predadores possam exercer efeitos distintos sobre o comportamento de fitófagos e polinizadores e parasitoides, pouco se sabe sobre seus efeitos no comportamento de risco dessas três guildas em um mesmo sistema. Nós verificamos o contraste no comportamento forrageiro de fitófagos, polinizadores e parasitoides, manipulando uma atmosfera de risco de predação em ramos reprodutivos de Trichogoniops adenantha(DC) na Serra do Japi, Jundiaí, SP. Para isso, comparamos o número de visitas a flores com e sem predadores. Adicionalmente, utilizamos duas espécies de aranhas, Peucetia rubrolineata (Oxyopidae) e Misumenops argenteus (Thomisidae), que adotam estratégias distintas de caça e usam diferentes partes da planta como sítios de forrageamento, o que pode variar a vulnerabilidade dos visitantes a experiências que remetem ao perigo frente a predadores.Fitófagos manifestaram uma diminuição de mais de 50% das visitas quando expostos a um predador, e evitaram indistintamente flores portando P. rubrolineata ou M. argenteus. Entre os polinizadores, o reconhecimento de predadores possui especificidades para táxons. Nesse caso, apenas as abelhas evitaram flores portando M. argenteus, o que provocou um decréscimo de 60% no número de suas vistas. Os resultados sugerem que a presença de grupos taxonômicos distintos nas diferentes guildas influenciou o efeito encontrado. Esses dados fornecem uma nova perspectiva para os estudos de risco de predação, demonstrando que o efeito de predadores pode ser distinto conforme a guilda observada no sistema. Como diferentes guildas podem trazer efeitos distintos para o sucesso reprodutivo da planta, é importante contemplar o contraste de efeitos do comportamento de risco entre guildas em estudos que enfoquem cascatas tróficas. O resultado diferencial observado para as diferentes guildas observadas, fitófagos, polinizadores e parasitóides, em especial, o fato da presença das aranhas negativa para...
Keywords: Arachnida; Aracnideo; Animais - Alimentos; Polinizadores; Plantas - Reprodução; Japi, Serra do (SP)